2022
DOI: 10.3389/fonc.2022.880459
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of a Ferroptosis-Related lncRNA Signature for Predicting Prognosis and Immune Landscape in Osteosarcoma

Abstract: Research on the implications of ferroptosis in tumors has increased rapidly in the last decades. There are evidences that ferroptosis is involved in several aspects of cancer biology, including tumor progression, metastasis, immunomodulation, and therapeutic response. Nonetheless, the interaction between ferroptosis-related lncRNAs (FRLs) and the osteosarcoma immune microenvironment is poorly understood. In this study, a risk model composed of FRLs was developed using univariate and LASSO Cox regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 101 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…Through online prediction as well as correlation, expression, and survival analysis screening, we finally identified miR-26a-5p as the most potential upstream miRNA of EZH2, which is also consistent with a previous study [ 56 ]. Similarly, it has been shown that WASIR2 knockdown suppressed the malignant activity of osteosarcoma cells; RPARP-AS1 and GAS5 can be used as prognostic biomarkers for lung adenocarcinoma (LUAD) and PCa, respectively [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through online prediction as well as correlation, expression, and survival analysis screening, we finally identified miR-26a-5p as the most potential upstream miRNA of EZH2, which is also consistent with a previous study [ 56 ]. Similarly, it has been shown that WASIR2 knockdown suppressed the malignant activity of osteosarcoma cells; RPARP-AS1 and GAS5 can be used as prognostic biomarkers for lung adenocarcinoma (LUAD) and PCa, respectively [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have analyzed differentially expressed genes and long non-coding RNAs (lncRNAs) during ferroptosis in OS through bioinformatics, and finally identified 26 genes associated with OS prognosis ( 69 73 ) (CBS, EGFR, COCS1, PTN, PGD, ZEP36, DLL1, EOMES, ERCC2, G6PD, MYC, SLC39A8, etc.) and 8 lncRNAs ( 74 , 75 ) (RPARP-AS1, PARD6G-AS1, GAS5, UNC5B -AS1, LINC01060, AC124798.1, AC090559.1, and AC104825.1), which created a new prognostic model for OS patients. In-depth analysis of ferroptosis genes related to OS prognosis through a large database can not only provide directions for basic research but also provide more possibilities for subsequent clinical treatment of OS.…”
Section: Research Progress On Ferroptosis In Osteosarcomamentioning
confidence: 99%
“…A high-risk score was indicative of a poorer prognosis than a low-risk score. Many risk models have been developed for OS currently, such as necroptosis-associated lncRNA signature [24] ), ferroptosis-related lncRNA signature [25] , lipid-metabolism gene signature [26] , and pyroptosis-related gene signature [27] , however, our study arrived at a unique conclusion compared to the above studies. The results of our 3-year ROC analysis (AUC = 0.84) confirmed that the signature could have accurate and sensitive predictive efficacy.…”
Section: Discussionmentioning
confidence: 61%